Fracture behaviour of fly-ash filled FRP composites - Srivastava V.K.; Shembekar P.S.; Prakash R. (My University, 2025)
The major objective of this study was to determine the fracture toughness and fracture surface energy of epoxy, epoxy/fly-ash, epoxy/carbon fibre, epoxy/carbon fibre/fly-ash, epoxy/glass fibre and epoxy/glass fibre/fly-ash composites. The quality of composite specimens was evaluated by the ultrasonic method. The results show that a fly-ash particle can arrest the crack path and thus improve the fracture properties of fibre reinforced plastic (FRP) composites. The results of this study have further significance in view of the fact that fly-ash powder is far cheaper than carbon fibre, glass fibre and epoxy resin. © 1988.